Judging the Secret Thoughts of All: Functional Neuroimaging, 'Brain Reading', and the Theological Ethics of Privacy1. (February 2021) - Messer, Neil
Of the many futuristic prospects offered by neuroscience, one of the more controversial is 'brain reading': the use of functional neuroimaging to gain information about subjects' mental states or thoughts. This technology has various possible applications, including 'neuromarketing' and lie detection. Would such applications violate subjects' privacy rights? Conversely, if God knows and judges all our secret thoughts, do Christians have any stake in defending a right to mental privacy? This article argues that God's knowledge of us is different not only in degree but in kind from the knowledge sought through brain reading. This view of divine knowledge supports a theological account of privacy, richer and broader in scope than standard accounts of privacy rights, which can aid the ethical analysis of the use of brain reading technology for purposes such as marketing and lie detection.